Clinical efficacy and safety of Huachansu injection combination with platinum-based chemotherapy for advanced non-small cell lung cancer: A systematic review and meta-analysis of randomized controlled trials. Issue 36 (10th September 2021) - Tan, Xinmei; Liang, Xueyan; Xi, Jiaxi; Guo, Sitong; Meng, Mingyu; Chen, Xiaoyu; Li, Yan
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Huachansu injection (HCS) is a widely used traditional Chinese medicine for advanced non-small cell lung cancer (NSCLC) to alleviate the adverse drug reactions (ADRs) and enhance the clinical efficacy of chemotherapy. Objective: To evaluate the efficacy and safety of HCS as an adjunctive treatment to platinum-based chemotherapy (PBC) for advanced NSCLC. Methods: A systematic review and meta-analysis were conducted according to PRISMA guidelines. A total of nine databases were searched to select randomized controlled trials (RCTs) of HCS plus PBC to treat NSCLC from inception to October 10, 2020. RCTs on HCS plus PBC vs PBC alone for advanced NSCLC were included. Dichotomous data were pooled as risk ratio (RR) with 95% confidence intervals. RCTs compared to HCS plus PBC vs PBC alone were included. Primary outcomes were objective response rate (ORR) and disease control rate (DCR), and secondary outcomes were survival rate, quality of life (QOL), and adverse drug reactions (ADRs). GRADE software was used to access the quality of evidence. Results: A total of 32 RCTs, including 2753 patients, were included. Compared to PBC alone, HCS plus PBC improved the ORR, DCR, 1- and 2-year survival rates, and QOL and alleviated neutropenia, thrombocytopenia, nausea, vomiting, anemia, liver injury, renal injury, and alopecia. Conclusions: Compared to PBC alone, HCS plus PBC improved the clinical efficacy and alleviated the ADRs in advanced NSCLC patients. Considering the limitations of the included RCTs, high-quality trials with longer follow-ups are needed to further confirm the results.